Strengthening Green Islamic Values to Realize Eco-Pesantren: A Study on the Tahfidzul Qur'an Islamic Boarding School of Integrated Islamic Boarding School - Sofiyana Khoirunnisa; Irfan Abu Nazar; Hashfi Hawali Abdul Matin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Islamic boarding schools, as Islamic educational institutions, have a strategic role in shaping the character of caring for the environment through the integration of Islamic values in daily life. One approach that can be applied is to strengthen Green Islamic values to realize the concept of Eco-Pesantren. The Tahfidzul Qur'an Islamic Boarding School of SMA IT Ibnu Abbas Klaten has the potential to develop this concept; however, not all aspects of environmental management are optimal, particularly in waste management, the internalization of ecotheological attitudes, and the active involvement of students. This study aims to: (1) Describe the actual condition of environmental management, especially waste management, at the Tahfidzul Qur'an Islamic Boarding School of SMA IT Ibnu Abbas Klaten, (2) Analyze the understanding and attitude of students towards Green Islamic values, and (3) Formulate a strategy to strengthen Green Islamic values towards Eco-Pesantren. This study employs a mixed-methods approach, incorporating in-depth interviews, observations, and documentation methods. The analysis is conducted through a SWOT approach, which combines internal and external factors, as well as supporting theories such as Islamic Ecotheology, Environmental Literacy, and the Theory of Planned Behavior. The results of the study showed that the survey (n=126) yielded an average score of 4.3 (86.6%), indicating that students already possess a good theological understanding of the importance of protecting the environment as a form of servitude to Allah and as a responsibility of caliphs.